Developing voice and leadership amongst a group of class captains - Nehunga, Jacobina Taukondjele (Rhodes University, Faculty of Education, Department of Education, 2020)
The notion that leadership can be reduced to that of a formal position such as principalship has become problematic in school leadership research and practice, globally and also in Namibia. It appears that when leadership is concentrated only at the level of a principal within schools, teachers and learners within the same school experience a lack of opportunities to contribute to leadership practices, thus losing a sense of ownership. Supporting a distributed leadership perspective and embracing transformative leadership, this study investigated how learner voice and learner leadership (see for example Mitra and Gross, 2009) can be developed within a group of class captains in a combined school in rural Namibia. Cultural Historical Activity Theory (CHAT) underpinned the study which is located within a critical paradigm. Findings of the study were captured into two phases whereby phase one generated contextual profiling findings through the adoption of qualitative methods such as questionnaires, interviews, document analysis and two other participatory methods of mapping and transect walks. Phase two findings were captured through expansive learning actions in Change Laboratory Workshops. Observation notes, video recording and photographs and informal discussions were used as data sources during this phase. Both inductive and abductive analysis were employed. The findings revealed that a few enabling conditions to class captainship practice existed, but generally there was limited participation of class captains in school leadership. Class captains were seen as merely class representatives and their leadership was confined to a classroom level in the school. They performed more managerial tasks than leadership. It was also revealed that class captainship is not a documented practice in Namibia and it lacks support. Against this backdrop, during phase two of the study, seven contradictions were identified and two contradictions were prioritised for resolution during the Change Laboratory Workshops. Some of the resolutions included the development of a school based guiding document for class captains; an establishment of a class captainship club; and the promotion of a yearly election campaign of class captains. The study recommends more interventionist studies to be conducted on class captainship in order to see the practice documented in terms of policy in Namibia, perhaps in the near future.
Keywords: Educational leadership -- Namibia; Transformational leadership -- Namibia; Leadership in adolescents -- Namibia; Rural schools -- Namibia; School children --- Namibia -- Attitudes; School management and organization --- Namibia; Cultural Historical Activity Theory